Siri' Na Pacce as a Paradigm of Islamic Character Education Based on Local Culture in South Sulawesi - Hidayat, Muhammad Ilham; Rasyid, Musyrifah; Nurannisa, Ismi; Syahrul, M.; Tang, Muhammad (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research aims to examine the values of Siri' Na Pacce as a paradigm of Islamic character education based on local culture in South Sulawesi. Siri' Na Pacce is a philosophy of life for the Bugis-Makassar community that contains moral, social, and spiritual values such as self-esteem (siri') and social concern (pacce). This study uses a qualitative approach with the library research method, exploring various cultural, Islamic, and character education literature. The analysis was conducted descriptively and analytically to explore the relevance between Siri' Na Pacce values and the principles of Islamic character education. The research findings indicate that Siri' aligns with the Islamic concepts of 'izzah (self-respect) and haya' (shame toward sin), while Pacce reflects the values of rahmah (compassion) and ukhuwah islamiyah (Islamic brotherhood). These two values have great potential to be integrated into the Islamic character education curriculum thru curriculum approaches, habituation, and role modelling. Case studies in several Islamic educational institutions in South Sulawesi show that applying the values of Siri' Na Pacce can strengthen the character development of students to be honest, responsible, and caring toward others. Thus, Siri' Na Pacce is not only a local cultural heritage, but also a paradigm of Islamic character education that is contextual and relevant in addressing the moral challenges of the younger generation in the era of globalization.